A study of fears in the Indian setting - Prabhu GG (Journal of All India Institute of Speech and Hearing, 1972)
Fear Survey Schedules (FSS) have been employed both as research instrumentsas well as clinical assessment techniques. (Lang and Lazovik, 1963, Wolpe andLang, 1964, Geer, 1965, Manosovitz and Lanyon, 1965, Rubin, et ah, 1968, Braun andReynolds, 1969, and Rubin, era/., 1909). Wolpe, et al., (1968, p. 27) point out that it isoften astonishing to find out many areas of unadaptive anxiety in an individualwhich have eluded all other avenues of enquiry, come to light through the FSS. TheFSS by Wolpe and Lang (1964) has been used quite often in clinical situations,though Bernstein and Allen (1969) claim that its clinical bias has made it least popularand utilitarian when compared with the other fear survey schedules available.